Shampoo Science: A Review of the Physiochemical Processes behind the Function of a Shampoo. Issue 3 (5th January 2023) - Thompson, Courtney J.; Ainger, Nick; Starck, Pierre; Mykhaylyk, Oleksandr O.; Ryan, Anthony J.
Abstract: The components of a shampoo are selected specifically to carry out important roles within the formulation. They must be carefully considered as not only do they act to carry out their own function but they also influence the function of the other components through complexation and other physiochemical interactions. This review focuses on the four principal components in a commercial shampoo formulation: surfactant, deposition polymer, structuring polymer, and viscosity modifiers. The most common molecule types used commercially to carry out the specific roles are discussed, with each of their fundamental functions outlined in detail. The mechanisms by which these molecules can perform these roles are reviewed. Further consideration is taken to outline how components could interact with one another to hinder or facilitate processes. Abstract : The physiochemical process by which a shampoo functions are reliant on the composition of the formulation components. Understanding how these components interact forming complexes and the driving force behind their formation is crucial in formulation development. This review summarizes what is known in the personal care industry about such formulations and provides examples of the common components.